An Appraisal Analysis in the Novel Shine by Jessica Jung - Mega Putra, Rangga; Aini, Nurul; Dwi Agustina, Diyah (Bulletin of Science Education, 2024)
This research investigated to determine the type of Appraisal Attitude contained in a novel by Jessica Jung entitled "Shine". This study uses a qualitative approach. The source of the data in this study was a printed book from the novel Shine by Jessica Jung. Data collection techniques using document analysis techniques. Checking the validity of the data using source triangulation techniques. Data analysis techniques use qualitative data analysis techniques originating from Miles and Huberman. Consists of data collection, data reduction, data presentation, and drawing conclusions. The theory used in this study is Martin's theory which relates to the evaluation of the types of attitudes found in the text, the strength of the feelings involved and how the existing values can be integrated with the reader. The research data consisted of 200 sentences collected using document analysis techniques. The results showed that the most dominant type of attitude appraisal in Shine's novel was positive appraisal with 48 sentences (22.2%). Meanwhile there were 44 sentences (21.7%) which were placed as positive Affect, 42 sentences (20.3%) which were placed as negative Affect, 31 sentences (13.8%) which were placed as negative Appreciation, 11 sentences (10, 5%) which are classified as positive judgments, and 24 sentences (11.5%) which are positioned as negative judgments. Keywords: Appraisal Analysis, Analysis Novel Shine, Appraisal Attitude